Association of Human Immunodeficiency Virus Infection and Risk of Peripheral Artery Disease. Issue 3 (17th July 2018) - Beckman, Joshua A.; Duncan, Meredith S.; Alcorn, Charles W.; So-Armah, Kaku; Butt, Adeel A.; Goetz, Matthew Bidwell; Tindle, Hilary A.; Sico, Jason J.; Tracy, Russel P.; Justice, Amy C.; Freiberg, Matthew S.
Abstract : Background: The effect of human immunodeficiency virus (HIV) on the development of peripheral artery disease (PAD) remains unclear. We investigated whether HIV infection is associated with an increased risk of PAD after adjustment for traditional atherosclerotic risk factors in a large cohort of HIV-infected (HIV+) and demographically similar HIV-uninfected veterans. Methods: We studied participants in the Veterans Aging Cohort Study from April 1, 2003 through December 31, 2014. We excluded participants with known prior PAD or prevalent cardiovascular disease (myocardial infarction, stroke, coronary heart disease, and congestive heart failure) and analyzed the effect of HIV status on the risk of incident PAD events after adjusting for demographics, PAD risk factors, substance use, CD4 cell count, HIV-1 ribonucleic acid, and antiretroviral therapy. The primary outcome is incident peripheral artery disease events. Secondary outcomes include mortality and amputation in subjects with incident PAD events by HIV infection status, viral load, and CD4 count. Results: Among 91 953 participants, over a median follow up of 9.0 years, there were 7708 incident PAD events. Rates of incident PAD events per 1000 person-years were higher among HIV+ (11.9; 95% confidence interval [CI], 11.5–12.4) than uninfected veterans (9.9; 95% CI, 9.6–10.1). After adjustment for demographics, PAD risk factors, and other covariates, HIV+ veterans had an increased risk of incident PAD events compared with uninfected veterans (hazard ratio [HR], 1.19; 95% CI, 1.13–1.25). This risk was highest among those with time-updated HIV viral load >500 copies/mL (HR, 1.51; 95% CI, 1.38–1.65) and CD4 cell counts <200 cells/mm 3 (HR, 1.91; 95% CI, 1.71–2.13). In contrast, HIV+ veterans with time updated CD4 cell count ≥500 cells/mm 3 had no increased risk of PAD (HR, 1.03; 95% CI, 0.96–1.11). Mortality rates after incident PAD events are high regardless of HIV status. HIV infection did not affect rates of amputation after incident PAD events. Conclusions: Infection with HIV is associated with a 19% increased risk of PAD beyond that explained by traditional atherosclerotic risk factors. However, for those with sustained CD4 cell counts <200 cells/mm 3, the risk of incident PAD events is nearly 2-fold higher whereas for those with sustained CD4 cell counts ≥500 cells/mm 3 there is no excess risk of incident PAD events compared with uninfected people. Abstract : Supplemental Digital Content is available in the text.